1998
DOI: 10.1161/01.cir.98.9.833
|View full text |Cite
|
Sign up to set email alerts
|

Low-Energy Atrial Defibrillation

Abstract: T emporary epicardial wire electrodes placed during open heart surgery for potential diagnostic and/or therapeutic use in patients in the immediate postoperative period have been used safely and effectively as part of standard care for a long time. [1][2][3][4] We have also known that synchronized delivery of a low-energy DC shock for cardioversion of atrial fibrillation is very effective. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] With the presentation by Liebold et al 22 of the study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1999
1999
2000
2000

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
(46 reference statements)
0
1
0
1
Order By: Relevance
“…However, more recent studies, using leads with a larger surface area, right atrial to coronary sinus configuration (Figure 6), and biphasic waveforms, have been successful 38,39 . A recent review of the world experience has shown that low energy defibrillation is feasible and safe 40 . A total of 1212 shocks was reported.…”
Section: Pharmacological Therapymentioning
confidence: 99%
“…However, more recent studies, using leads with a larger surface area, right atrial to coronary sinus configuration (Figure 6), and biphasic waveforms, have been successful 38,39 . A recent review of the world experience has shown that low energy defibrillation is feasible and safe 40 . A total of 1212 shocks was reported.…”
Section: Pharmacological Therapymentioning
confidence: 99%
“…Tanto la caracterización de la arritmia a partir del ECG de superficie o de los registros endocavitarios, como la predicción de los cambios en el patrón fibrilatorio inducidos por fármacos u otros procedimientos, son útiles para perfeccionar los algoritmos de identificación de la arritmia en diversas situaciones y contextos [Waldo 1998, Jetova & Mitev 2002, Kaup et al 2004.…”
Section: Aplicaciones Clínicas De Los Estudios Sobre La Fvunclassified